2020
DOI: 10.1371/journal.pone.0227613
|View full text |Cite
|
Sign up to set email alerts
|

A brain connectivity characterization of children with different levels of mathematical achievement based on graph metrics

Abstract: Recent studies aiming to facilitate mathematical skill development in primary school children have explored the electrophysiological characteristics associated with different levels of arithmetic achievement. The present work introduces an alternative EEG signal characterization using graph metrics and, based on such features, a classification analysis using a decision tree model. This proposal aims to identify group differences in brain connectivity networks with respect to mathematical skills in elementary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…The correlation between fronto-parietal connectivity and mathematics was also reported for EEG recorded in other mathematical tasks. For example, the fronto-parietal coherence ( González-Garrido et al, 2018 ) and frontal/parietal based coherence networks ( Torres-Ramos et al, 2020 ) in a numerical comparison task are correlated with different levels of mathematical achievement in children, and the fronto-parietal power correlation in a logical-mathematical task is correlated with the behavioral outcome of the task in adults ( Molina del Río et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between fronto-parietal connectivity and mathematics was also reported for EEG recorded in other mathematical tasks. For example, the fronto-parietal coherence ( González-Garrido et al, 2018 ) and frontal/parietal based coherence networks ( Torres-Ramos et al, 2020 ) in a numerical comparison task are correlated with different levels of mathematical achievement in children, and the fronto-parietal power correlation in a logical-mathematical task is correlated with the behavioral outcome of the task in adults ( Molina del Río et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies included in the current review, LOOCV was the most widely adopted (21 studies), while most other studies used 10-fold CV (10 studies). Although a recent study suggested that repetitive cross-validation is more reliable than the leave-one-out method (Valente et al, 2021), this technique was only adopted in three studies (Litwińczuk et al, 2023;Nemmi et al, 2023;Torres-Ramos et al, 2020). Overall, there is wide variability in the machine-learning techniques used in neuroimaging studies, both in terms of algorithm selection and CV method.…”
Section: Studies Use a Range Of Machine Learning Methodsmentioning
confidence: 99%
“…Although our findings should be interpreted with caution, they contribute to the rapidly growing literature showing that machine learning classification of dyslexia based on features extracted from the EEG holds considerable promise-in particular, when classification is based on tasks specifically designed to examine those processes that are thought to be compromised in dyslexia. A recent study focusing on mathematical achievement provides an interesting illustration of such an approach [75]. This study included children who scored low, average, or high on the math section of an achievement test and were asked to perform a numerical comparison task while their EEG was recorded.…”
Section: Classifiermentioning
confidence: 99%